Colonization of plant substrates at hydrothermal vents and cold seeps in the northeast Atlantic and Mediterranean and occurrence of symbiont-related bacteria - Szafranski, Kamil M.; Deschamps, Philippe; Cunha, Marina R.; Gaudron, Sylvie M.; Duperron, Sébastien (Frontiers in Microbiology, 2015)
Reducing conditions with elevated sulphide and methane concentrations in ecosystems such as hydrothermal vents, cold seeps or organic falls, are suitable for chemosynthetic primary production. Understanding processes driving bacterial diversity, colonization and dispersal is of prime importance for deep-sea microbial ecology. This study provides a detailed characterization of bacterial assemblages colonizing plant-derived substrates using a standardised approach over a geographic area spanning the North-East Atlantic and Mediterranean. Wood and alfalfa substrates in colonization devices were deployed for different periods at 8 deep-sea chemosynthesis-based sites in 4 distinct geographic areas. Pyrosequencing of a fragment of the 16S rRNA-encoding gene was used to describe bacterial communities. Colonization occurred within the first 14 days. The diversity was higher in samples deployed for more than 289 days. After 289 days, no relation was observed between community richness and deployment duration, suggesting that diversity may have reached saturation sometime in between. Communities in long-term deployments were different, and their composition was mainly influenced by the geographical location where devices were deployed. Numerous sequences related to horizontally-transmitted chemosynthetic symbionts of metazoans were identified. Their potential status as free-living forms of these symbionts was evaluated based on sequence similarity and monophyly with demonstrated symbionts. Results suggest that some free-living forms of metazoan symbionts or their close relatives, such as the epsilonproteobacterium associated with the shrimp Rimicaris exoculata, are efficient colonizers of plant substrates at vents and seeps.